CAUSAL FACTORS OF THE PARTNER AND SUPPLY CHAIN RELATIONSHIP AFFECTING SUPPLY CHAIN PERFORMANCE MANAGEMENT AND CUSTOMER SERVICE MATURITY LEVEL IN THE AIR CONDITIONING MANUFACTURING BUSINESS - Valantgul, Sookkhasakon (Journal of Buddhist Anthropology, 2022)
The objectives of the research article were: 1) to study the causal factors of partner relationships and supply chains that affect supply chain performance and customer service maturity level 2) to study the influence of causal factors on partner relationships and supply chains that affect supply chain performance and customer service maturity level and 3) to create model about causal factors of partner relationships and supply chains that affect supply chain performance and customer service maturity level. This was mixed method research which used a quantitative specific randomized questionnaire. The sample was collected from executives, supervisors and operators of all 660 persons. The data were analyzed by using frequency, percentage, mean, standard deviation, skew, kurtosis, and using qualitatively specific randomized in-depth interview. The key informant was collected by: 1) raw material supplier, 2) producer, 3) wholesalers, 4) retailers, and 5) consumer of all 5 persons. The result found that content analysis were and Overview as follows: 1) the overview of the factors of partner relationships was at high level ( = 3.70, S.D.= 0.88), the highest average was business development ( = 3.74, S.D.= 0.64), followed by sales and distribution channels ( = 3.73, S.D.= 0.78), and the least is product development ( = 3.62, S.D.= 0.80). 2) The causal factor influence was direct influence such as partner relationships, supply groups and partners, supply chain relationship, supply chain performance management and indirect influence. The partner relationship was statistically significant at 0.01 levels and 3) The model had harmonious and influential in every aspect, Chi-Square = 288.12, df = 256, p = 0.082, GFI = 0.97, AGFI = 0.94, SRMR= 0.012, RMSEA = 0.014 and CFI = 1.00. It was considered that the model was suitable and acceptable.